Semen characteristics and malondialdehyde levels in men with different reproductive problems. (20th October 2014) - Collodel, G.; Moretti, E.; Micheli, L.; Menchiari, A.; Moltoni, L.; Cerretani, D.
Summary: The aim of this study was to assess the level of malondialdehyde (MDA) in the seminal plasma of infertile men and to highlight a relationship between the level of MDA and semen parameters. Eighty‐one infertile patients were divided into groups according to their clinical diagnosis: genitourinary infections, varicocele and idiopathic infertility. Semen quality was assessed by light and transmission electron microscopy (TEM). TEM data were quantified with a mathematical formula able to obtain a fertility index and the percentage of sperm apoptosis, immaturity, and necrosis. Seminal MDA levels were determined by spectrofluorometry. Scrotal Eco‐color Doppler was used to detect the varicocele. Infected patients had a positive bacteriological semen analysis. A control group consisted of 14 normospermic fertile men. Fertile group showed significantly increased values of sperm concentration, motility, and fertility index compared to infertile groups. In the infertile groups, sperm motility, concentration, apoptosis, and fertility index were not significantly different. In infection group, the percentage of necrosis was significantly higher than that observed in fertile men, varicocele, and idiopathic infertility groups ( p  < 0.001). MDA levels increased significantly in infection group in comparison with varicocele group ( p  < 0.01), idiopathic infertility group, and fertile men ( p  < 0.001) and in varicocele group compared to idiopathic infertility group ( p  < 0.001). In infection group, MDA levels positively correlated with sperm concentration ( p  < 0.01), fertility index ( p  < 0.05), and necrosis ( p  < 0.001), whereas a negative correlation was found with motility ( p  < 0.01). In varicocele group MDA levels correlated positively with necrosis and negatively with immaturity ( p  < 0.05). In fertile men and idiopathic infertility group, they did not show any correlation. In conclusion, we suggest that the evaluation of seminal MDA may be a good marker for understanding pathologies responsible of a sperm motility reduction such as urogenital infections or inflammatory status.